Characterization Of Phases and Structures In Composites By TEM and SEM - Ávalos, Agustín; Zelaya, Maria Eugenia; Esquivel, Marcelo Ricardo Oscar (Cambridge University Press, 2020)
Fil: Ávalos, Agustín. Universidad Nacional de San Martín. Instituto Sabato; Argentina